PENGARUH HARGA, KUALITAS PRODUK, DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA YOGYAKARTA DI SHOPEE - NURHAYATI, SITI (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
This research was conducted with the aim of knowing the effect of price, product quality, and discounts on purchasing decisions of Yogyakarta students at Shopee. This research method uses multiple linear regression analysis using SPSS version 28.0.1.1 for windows. The sample used in the study was 114 people. The sampling method uses accidental sampling technique Based on the results of the analysis there is a significant influence of price, product quality, and discounts on purchasing decisions. In addition, from this study it is also known that product quality dominates in influencing purchasing decisions. It is also known that all independent variables have a simultaneous effect on the dependent variable with a percentage of 54.6%. Purchase decisions (dependent variable) are influenced by independent variables while the remaining 45.4% are influenced by other variables not included in this research model.